1985
DOI: 10.1136/jcp.38.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of an enzyme linked immunosorbent assay for Clostridium perfringens type A enterotoxin.

Abstract: Confirmation of C perfringens food poisoning depends on the isolation of large numbers (> 106/g) of the organism from faecal specimens and the subsequent demonstration of a common serological type in these and in the incriminated food. The ability of these isolates to produce enterotoxin in vitro may be of importance, but the problems associated with obtaining good sporulation and subsequent enterotoxin production in vitro are well known and make this approach unsuitable.5 An alternative approach is to show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
4

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 18 publications
1
41
0
4
Order By: Relevance
“…However, Stringer, Watson & Gilbert (1982) reported that enterotoxigenicity in strains other than those associated with food poisoning is uncommon. With the advent of improved techniques for sporulation and the development of a highly sensitive and rapid technique (ELISA) for the detection of enterotoxin (Bartholomew et al 1985) an investigation of the potential for toxin production by normal flora isolates would be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Stringer, Watson & Gilbert (1982) reported that enterotoxigenicity in strains other than those associated with food poisoning is uncommon. With the advent of improved techniques for sporulation and the development of a highly sensitive and rapid technique (ELISA) for the detection of enterotoxin (Bartholomew et al 1985) an investigation of the potential for toxin production by normal flora isolates would be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore recommended that the investigation of outbreaks in such places should include an extensive epidemiological investigation. More recently, Bartholomew et al (1985) have shown that the detection of C. perfringens enterotoxin in faecal specimens obtained within two days of the onset of symptoms typical of C. perfrinqens food poisoning is a specific and significant finding. It is suggested that where possible the presence of enterotoxin in faeces be considered as an important additional criterion to those previously mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Those high CPE dose effects could be transiently blocked by the oncosis inhibitor glycine, but not by caspase 3/7 or caspase 1 inhibitors. As CPE concentrations similar to those inducing apoptosis or oncosis in CaCo-2 cells have been detected in the diarrhoeic feces of people ill with CPE-associated GI disease (Batholomew et al ., 1985;Birkhead et al ., 1988), CPE dose-dependent selection of cell death pathways appears pathophysiologically relevant for understanding CPE action in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Outra vantagem da PCR em relação aos métodos convencionais é a sua maior sensibilidade e o fato de dispensar o uso de animais para detecção de toxinas, resolvendo problemas bioéticos (Bartholomew et al, 1995;Uzal et al, 1997).…”
unclassified